Immunization with the Malaria Diversity-Covering Blood-Stage Vaccine Candidate Plasmodium falciparum Apical Membrane Antigen 1 DiCo in Complex with Its Natural Ligand PfRon2 Does Not Improve the In Vitro Efficacy - Spiegel, Holger; Boes, Alexander; Fendel, Rolf; Reimann, Andreas; Schillberg, Stefan; Fischer, Rainer (Frontiers in Immunology, 2017)
The blood-stage malaria vaccine candidate Plasmodium falciparum apical membrane antigen 1 (PfAMA1) can induce strong parasite growth-inhibitory antibody responses in animals but has not achieved the anticipated efficacy in clinical trials. Possible explanations in humans are the insufficient potency of the elicited antibody responses, as well as the high degree of sequence polymorphisms found in the field. Several strategies have been developed to improve the cross-strain coverage of PfAMA1-based vaccines, whereas innovative concepts to increase the potency of PfAMA1-specific IgG responses have received little attention even though this may be an essential requirement for protective efficacy. A previous study has demonstrated, that immunization with a complex of PyAMA1 and PyRON2, a ligand with an essential functional role in erythrocyte invasion, leads to protection from lethal Plasmodium yoelli challenge in an animal model and suggested to extend this strategy towards improved strain coverage by using multiple PfAMA1 alleles in combination with PfRon2L. As an alternative approach along this line we decided to use PfRon2L in combination with three PfAMA1 diversity covering variants (DiCo) to investigate the potential of this complex to induce more potent parasite growth inhibitory immune response in combination with better cross-strain-specific efficacy. Within the limits of the study design, the ability of the PfAMA1 DiCo-Mix to induce cross-strain-specific antibodies was not affected in all immunization groups, but the DiCo-PfRon2L complexes did not improve the potency of PfAMA1-specific IgG responses.